2022
DOI: 10.1371/journal.pgph.0000600
|View full text |Cite|
|
Sign up to set email alerts
|

Aging and hypertension among the global poor—Panel data evidence from Malawi

Abstract: Hypertension is a rapidly growing disease burden among older persons in low-income countries (LICs) that is often inadequately diagnosed and treated. Yet, most LIC research on hypertension is based on cross-sectional data that does not allow inferences about the onset or persistence of hypertension, its correlates, and changes in hypertension as individuals become older. The Mature Adults Cohort of the Malawi Longitudinal Study of Families and Health (MLSFH-MAC) is used to provide among the first panel analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Also, having unimproved toilet type in households was associated with increased SBP while using primitive fuel for cooking in households was associated with decreased DBP. Our finding that older ages was associated with increased SBP and DBP is not surprising because generally the older the age, the higher the chance of one developing hypertension and this is consistent with previous studies that found that high blood pressure increase with an increasing age [12,13,18,[29][30][31]. Consistent with previous studies that reported increase in hypertension prevalence among those who are obese [12,13,30,31], being obese was associated with increased SBP and DBP PLOS GLOBAL PUBLIC HEALTH in this study.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, having unimproved toilet type in households was associated with increased SBP while using primitive fuel for cooking in households was associated with decreased DBP. Our finding that older ages was associated with increased SBP and DBP is not surprising because generally the older the age, the higher the chance of one developing hypertension and this is consistent with previous studies that found that high blood pressure increase with an increasing age [12,13,18,[29][30][31]. Consistent with previous studies that reported increase in hypertension prevalence among those who are obese [12,13,30,31], being obese was associated with increased SBP and DBP PLOS GLOBAL PUBLIC HEALTH in this study.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…Our finding that older ages was associated with increased SBP and DBP is not surprising because generally the older the age, the higher the chance of one developing hypertension and this is consistent with previous studies that found that high blood pressure increase with an increasing age [12,13,18,[29][30][31]. Consistent with previous studies that reported increase in hypertension prevalence among those who are obese [12,13,30,31], being obese was associated with increased SBP and DBP PLOS GLOBAL PUBLIC HEALTH in this study. Obesity and age were reported to be the most powerful factors associated with hypertension in previous studies [12,18,29,30].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 1 more Smart Citation
“…However, studying global poor populations is important because the world's aging populations are increasingly concentrated in such contexts and the different socioeconomic contexts may have implications for health across the lifecourse. For example, in our study population, high blood pressure is common among older individuals despite the lack of conventional risk factors such as obesity or access to Western-type diets (Kohler et al 2020(Kohler et al , 2022b; NCD Risk Factor Collaboration (NCD-RisC) 2021). Declines in physical and mental health occur on average in this cohort at younger ages as compared to individuals in HICs (Kohler et al 2022a(Kohler et al , 2023, and similar patterns of early health declines have been documented in other populations exposed to significant lifecourse adversities (Geronimus et al 2006;Phelan and Link 2015;Simons et al 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Currently, remaining life expectancy at age 45 is ≈28 years (UN Population Division 2019) and healthy life expectancy is ≈22 years (GBD 2019 Disease Collaboration 2020). Older adults aged 45+ years can expect to live a large proportion of their remaining life expectancy subject to physical and mental health limitations impacting their daily activities and overall wellbeing (Kohler et al 2017(Kohler et al , 2022a(Kohler et al , 2022b(Kohler et al , 2023Payne, Mkandawire, and Kohler 2013). HIV/AIDS remains widespread, with a prevalence of about 7.4 percent among rural adults 15-49 years old (Malawi DHS 2017).…”
Section: Introductionmentioning
confidence: 99%